Navajo suicide a multitrait-multilanguage approach to translation equivalence - Enriquez, Virgilio G. (Philippine Journal of Psychology, 1971)
Forty-nine Najavo-English bilinguals took both an English and a Navajo version of a taped suicide inventory. The back translation was used to maximize content equivalence and to lessen interpretation difficulties culturo-linguistic differences were isolated through the use multitrait-multilanguage approach. The construction od a multitrait-multilanguage square matrix provided for a translation equivalence index.